2013
DOI: 10.1371/journal.pone.0060537
|View full text |Cite|
|
Sign up to set email alerts
|

Why Can’t Rodents Vomit? A Comparative Behavioral, Anatomical, and Physiological Study

Abstract: The vomiting (emetic) reflex is documented in numerous mammalian species, including primates and carnivores, yet laboratory rats and mice appear to lack this response. It is unclear whether these rodents do not vomit because of anatomical constraints (e.g., a relatively long abdominal esophagus) or lack of key neural circuits. Moreover, it is unknown whether laboratory rodents are representative of Rodentia with regards to this reflex. Here we conducted behavioral testing of members of all three major groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
132
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 66 publications
(90 reference statements)
3
132
0
1
Order By: Relevance
“…However, it should be noted that the relationship between anxiety and nausea is based primarily on the higher probability of occurrence of nausea in subjects with higher anxiety levels [2,21,23,37,42], and correlations between degree of anxiety and magnitude of nausea are weak [27,44]; the present A C C E P T E D M A N U S C R I P T study only models the latter situation. Taking the results at face value, motion clearly produced hypothermia in all three lines, and this is consistent with previous studies of hypothermia induced by a number of emetic stimuli in both rats (lacking an emetic reflex [19]) and Suncus murinus (with an emetic reflex) [9,17,35]. (and bradycardia) response in LAB compared to HAB and NAB is due to an increased sensitivity in the vestibular-thermoregulatory/cardiovascular pathways that are psychogenetically selected by the elevated plus-maze test.…”
Section: Do Our Findings Challenge the Validity Of The "Hypothermia Nsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it should be noted that the relationship between anxiety and nausea is based primarily on the higher probability of occurrence of nausea in subjects with higher anxiety levels [2,21,23,37,42], and correlations between degree of anxiety and magnitude of nausea are weak [27,44]; the present A C C E P T E D M A N U S C R I P T study only models the latter situation. Taking the results at face value, motion clearly produced hypothermia in all three lines, and this is consistent with previous studies of hypothermia induced by a number of emetic stimuli in both rats (lacking an emetic reflex [19]) and Suncus murinus (with an emetic reflex) [9,17,35]. (and bradycardia) response in LAB compared to HAB and NAB is due to an increased sensitivity in the vestibular-thermoregulatory/cardiovascular pathways that are psychogenetically selected by the elevated plus-maze test.…”
Section: Do Our Findings Challenge the Validity Of The "Hypothermia Nsupporting
confidence: 92%
“…We have recently demonstrated that similar hypothermic responses are present in rats (lacking an emetic reflex [19]) and in house musk shrews (Suncus murinus, an insectivore possessing emetic reflex) [9,35]. We have proposed, based on several arguments, that the drop in body temperature might represent a biomarker of a nausea-like state in laboratory animals.…”
Section: Introductionmentioning
confidence: 96%
“…However, rodents lack the vomiting reflex, and this precludes them from getting as malnourished and dehydrated as seen in human infants with this condition (12,43).…”
Section: Discussionmentioning
confidence: 99%
“…Some reasons for the inability to vomit are: 1) diaphragmatic structure relatively less muscular 3,12 ; 2) esophagus length relatively longer than non-emetic species 13 ; 3) stomach geometry with absence of a funnel shape 3 ; 4) absent brainstem neurological component of vomit 3,14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that small murines, such as rats and mice, do not exhibit the ability to vomit, and in case of fasting they have an eating disorder that involves the appetite perversion, demonstrated by eating non-food substances, such as soil and their bedding 2,3 . Thus, food deprivation becomes just a stress for the animal trial, and can influence in some experiments because of the changes in carbohydrate metabolism 4 .…”
Section: Introductionmentioning
confidence: 99%